2018
DOI: 10.2147/tcrm.s181043
|View full text |Cite
|
Sign up to set email alerts
|

Selection of glucocorticoid-sensitive patients in interstitial lung disease secondary to connective tissue diseases population by radiomics

Abstract: PurposeThe effect of glucocorticoid(s) on connective tissue disease (CTD)-related interstitial lung disease (ILD) is controversial. This multicenter study aimed to identify glucocorticoid-sensitive patients using a radiomics approach.MethodsA total of 416 CTD-ILD patients who began glucocorticoid treatment at the discretion of the attending physician, with or without cyclophosphamide, were included in this study. High doses were defined as pulsed intravenous methylprednisolone, an initial dose of 1 mg/kg/day o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Researchers used radiomics method to seek association between hidden information in medical images and clinical data, to enrich diagnosis ability for radiologists, and to show advantages in prognostic power. For example, Feng et al 32 suggested that radiomics‐based predictive models reliably identified glucocorticoid‐sensitive CTD‐ILD patients. Therefore, high‐throughput (3234 radiomics features) and high‐dimensional texture features of lesions were extracted, which may reflect the underlying histological differences between PI and CAP.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers used radiomics method to seek association between hidden information in medical images and clinical data, to enrich diagnosis ability for radiologists, and to show advantages in prognostic power. For example, Feng et al 32 suggested that radiomics‐based predictive models reliably identified glucocorticoid‐sensitive CTD‐ILD patients. Therefore, high‐throughput (3234 radiomics features) and high‐dimensional texture features of lesions were extracted, which may reflect the underlying histological differences between PI and CAP.…”
Section: Discussionmentioning
confidence: 99%
“…Kloth et al noted differences in texture analysis parameters between active alveolitis and lung fibrosis in chest CT scans of patients with systemic sclerosis (30). Feng et al reported that radiomicsbased predictive models reliably identified patients with glucocorticoid-sensitive connective tissue disease-associated interstitial lung disease (31). Another study showed that these models could be used to differentiate primary progressive pulmonary tuberculosis from community- acquired pneumonia in children (32).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study applied radiomics-based predictive models using random forest (RF) and kNN classifiers to identify glucocorticoid-sensitive connective tissue disease-related interstitial lung disease, obtaining AUC of 0.66 in RF models and 0.61 in kNN model. 32 Zhang et al 33 incorporated CT-radiomics and PET metabolic parameters to build a classification model (using a SVM method) for distinguishing benign and malignant lung lesions. Their model showed a substantial diagnostic capacity.…”
Section: Discussionmentioning
confidence: 99%